2020
DOI: 10.3390/rs12060919
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Angle Effect of Leaf Reflectance Measured by Indoor Hyperspectral Light Detection and Ranging (LiDAR)

Abstract: Hyperspectral light detection and ranging (LiDAR) (HSL) combines the characteristics of hyperspectral imaging and LiDAR techniques into a single instrument without any data registration. It provides more information than hyperspectral imaging or LiDAR alone in the extraction of vegetation physiological and biochemical parameters. However, the laser pulse intensity is affected by the incident angle, and its effect on HSL has not yet been fully explored. It is important for employing HSL to investigate vegetatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The relationship between the backscatter intensity of the HSL and the incident angle and range is explored. The incidence angle and range experiments' results, carried out with different targets, demonstrated that the backscatter intensity recorded by the HSL (Figures 6 and 9) cannot follow the theoretical model, including the Lambertian model and the 1/R 2 relation model, which is consistent with some previous studies [27,46,47]. The laser backscatter intensities of targets with isotropically reflecting reflectance surfaces share a similar trend in the incidence angle and distance behavior and there seems to be no wavelength dependency on the scanning geometry effect.…”
Section: Discussionsupporting
confidence: 90%
“…The relationship between the backscatter intensity of the HSL and the incident angle and range is explored. The incidence angle and range experiments' results, carried out with different targets, demonstrated that the backscatter intensity recorded by the HSL (Figures 6 and 9) cannot follow the theoretical model, including the Lambertian model and the 1/R 2 relation model, which is consistent with some previous studies [27,46,47]. The laser backscatter intensities of targets with isotropically reflecting reflectance surfaces share a similar trend in the incidence angle and distance behavior and there seems to be no wavelength dependency on the scanning geometry effect.…”
Section: Discussionsupporting
confidence: 90%
“…The distribution density of leaf angle, one of canopy structure parameter, is highly related to the reflectance signals of HSL. Some relevant scholars have carried out preliminary exploration in the correction of factors such as distance and incident angle [45,50,53], but the impact assessment and model correction of complex canopy reflection characteristics need to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we set the angle threshold as 60° for the incidence angle calibration in this study during the scanning experiment. Hu et al [53] conducted the similar experiments on different leaves from 0° to 80° and they found the specular reflection was significant in red band, and its non-Lambertian characteristics are obvious. However, the reflectance characteristic in NIR band followed the Lambertscattering law, but little specular reflection was observed.…”
Section: Distance-angle Calibrationmentioning
confidence: 99%
“…2. Continuous/Full waveform LiDAR: When the entire waveform is saved as one unit, its a continuous or full form LiDAR [108]. A lot of LiDARs use this form of recording.…”
Section: Classifying the Lidarmentioning
confidence: 99%